Developing the ‘Beckett Digital Manuscript Project’ - Van Hulle, Dirk; Neyt, Vincent (Wiener Digitale Revue, 2020)
Dirk Van Hulle and Vincent Neyt report on the Beckett Digital Manuscript Project. Its purpose is to reunite the manuscripts of Samuel Beckett’s works in a digital way, and to facilitate genetic research: the project brings together digital facsimiles of documents that are now preserved in different holding libraries, and adds transcriptions of Beckett’s manuscripts, tools for bilingual and genetic version comparison, a search engine, and an analysis of the textual genesis of his works. Der Werkstattbericht von Vincent Neyt und Dirk van Hulle liefert Einblicke in das Beckett Digital Manuscript Project (BDMP), das Samuel Becketts weltweit verstreute Manuskripte im Hypertext vereinen wird. Das Projekt führt auf einzigartigem Weg digitale Faksimiles, Transkriptionen und textgenetische Auszeichnungen zusammen: Nicht umsonst gewann es 2018 den Modern Language Association Prize for a Bibliography.